Neonatal ulcera in the diaper area as an expression of hemangioma. - Bonifazi, E.; Milano, A. (European Journal of Pediatric Dermatology, 2010)
We observed an infant of 15 days with a left perianal ulceration, appeared at the age of 8 days in full health and not preceded by fever, infection, trauma or medication. Physical examination showed in the left perianal area a 4 cm long and 2 cm wide, more than 1 cm deep ulceration with irregular bottom. There were also two erosions, one on the right buttock, round, 2 cm in diameter and another on the left buttock, 4 cm x 3 (Fig. 1), both surrounded by reddish micropapules, reminiscent of a superficial hemangioma. Cultures from the bottom of the ulcer showed S. aureus and C. albicans. The child was medicated with antibiotic oint-ments. After 15 days, the ulcerated lesions healed with scarring, whereas in their surrounding area and on the scrotal region (Fig. 2) a superficial hemangioma got evident. Pelvic ultrasonography ruled out involvement of deep organs.